Inovasi Pembelajaran Bahasa Arab dengan Buku Digital Silsilah Allisan untuk Penutur Non-Arab - Faiqoh, Putri Kholida; Baity, Anggi Nurul (LPPM Universitas KH.A. Wahab Hasbullah, 2024)
Within the realm of Arabic language education, there are ongoing explorations of various challenges related to pedagogical methods and initiatives focused on developing effective solutions. One notable effort is the creation of a digital book on the Allisan Silsilah by Markaz Lisanul Umm. This study aims to examine and outline the process of learning Arabic among non-Arabic-speaking individuals in Indonesia using the Silsilah Allisan digital book. The study utilizes a descriptive qualitative approach, with the primary data sources being the educators and learners of Silsilah Allisan. Secondary data includes relevant articles and literature. The findings of this investigation indicate that Silsilah Allisan serves as an excellent representation of Arabic language learning. That includes practical and representative audio resources, exercises and kalam, qira'ah, and interactive kitabah facilitated through WhatsApp and Zoom groups. Additionally, proficient instructors in their respective disciplines are available to guide and assist.